Eleven-layer ultrahigh-barrier polyethylene low-carbon environment-friendly film material and preparation method thereof

By using flame retardant silane coupling agent to modify sodium-based vermiculite and EVOH in eleven-layer composite structure PE film materials in dairy packaging field, the problems of insufficient barrier performance and poor flame retardant performance of existing plastic packaging materials are solved, and the problem of insufficient barrier performance and poor flame retardant performance of existing plastic packaging materials is achieved. It has efficient dairy products with extended shelf life, reduced cost and environmental protection effects.

CN119283329AActive Publication Date: 2025-01-10SUZHOU ZIJIN PLASTIC

Patent Information

Application Number
CN202411239804.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-10
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The barrier performance of existing plastic packaging materials in the dairy packaging field is insufficient, and traditional plastics have poor flame retardant performance, which poses safety hazards. At the same time, the plastic recycling rate is low, resulting in environmental pollution and waste of resources.

Method used

A single PE film material with eleven-layer composite structure was designed. Sodium-based vermiculite was modified by synthesis of flame retardant silane coupling agent, and uniformly dispersed in ethylene-vinyl alcohol copolymer. Combined with EVOH, eleven-layer coextrusion was used. Prepared by blow molding film forming process, forming high-barrier, low-carbon environmentally friendly film materials for dairy product packaging.

Benefits of technology

It achieves ultra-high barrier performance, significantly extends the shelf life of dairy products, reduces dairy packaging costs, reduces aluminum consumption and carbon emissions, and promotes rapid recycling and reuse of plastics, improving packaging waste management efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119283329A_ABST
    Figure CN119283329A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of single PE eleven-layer composite structure thin film material research and development, and discloses an eleven-layer ultrahigh-barrier polyethylene low-carbon environment-friendly film material and a preparation method thereof.The preparation method comprises the steps that a DOPO-based silane coupling agent is synthesized, the surface of sodium-based vermiculite is modified with the DOPO-based silane coupling agent to obtain flame-retardant modified vermiculite, and the flame-retardant modified vermiculite is modified with the DOPO-based silane coupling agent to obtain the eleven-layer ultrahigh-barrier polyethylene low-carbon environment-friendly film material. And the flame-retardant modified vermiculite is uniformly dispersed in an ethylene-vinyl alcohol copolymer matrix to prepare the flame-retardant barrier material. A flame-retardant barrier material is introduced into a PE co-extrusion film, and an eleven-layer co-extrusion blow molding film forming process is adopted to prepare an eleven-layer composite structure film which is made of a single PE material and has the thickness of 50-200 microns. The invention provides a preparation method of a single PE material eleven-layer composite structure thin film, and an eleven-layer thin film single product is prepared, has excellent barrier performance, belongs to ultrahigh barrier materials, and can be used as an optimal alternative selection in the field of dairy product packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of research and development of single PE eleven-layer composite structure film materials, specifically to an eleven-layer ultra-high barrier polyethylene low-carbon environmentally friendly film material and a preparation method thereof. Background Art

[0002] With the increasing global attention to environmental protection, the food packaging industry is facing an urgent need to reduce plastic pollution. Plastic packaging materials with a single material are an environmentally friendly material that does not need to be sorted when recycled and can be recycled repeatedly, which is gradually becoming a development trend of the packaging industry.

[0003] The search found that the extension of the shelf life of boxed ambient temperature milk is mainly due to the barrier properties of the packaging box. The high-barrier film materials for food and drug packaging independently developed by domestic enterprises are expected to replace the existing milk packaging boxes. Among them, dairy packaging composite materials with a single all-plastic material (such as polyethylene) multi-layer composite structure composed of high-barrier films are expected to be used as the best alternative in the field of dairy product packaging. For example, the patent with publication number CN116604907A adds a small amount of EVOH barrier material to the polyethylene material and adopts a multi-layer co-extrusion method to prepare a single-material high-barrier recyclable composite film.

[0004] The search found that vermiculite is a natural layered silicate with high porosity and large specific surface area. By adding organically modified vermiculite to polymer matrix materials, the movement path of gas in the material can be changed, thereby significantly improving the barrier properties of the material. In addition, traditional plastic materials used for commodity packaging have poor flame retardant properties, are easy to burn, and pose safety hazards. Therefore, it is imperative to modify traditional plastics to be flame retardant. Summary of the invention

[0005] The present invention provides an eleven-layer film single product with a single all-plastic material (such as polyethylene, PE) multi-layer composite structure composed of a high-barrier film, which can be prepared into a green, low-carbon, environmentally friendly film material through a heat sealing tester and a multifunctional automatic film sealing machine, and is used in the field of dairy product packaging; on the one hand, the present invention achieves the technical improvement goal of reducing the cost of dairy product packaging by eliminating the aluminum foil structure, and on the other hand, achieves the technical improvement goal of reducing aluminum consumption and reducing carbon emissions by eliminating the aluminum foil structure. Thirdly, the use of a single all-plastic material multi-layer composite structure can promote the rapid recycling and reuse of plastics, thereby achieving the technical improvement goal of reducing packaging waste.

[0006] A method for preparing a single PE material eleven-layer composite structure film, comprising the following steps:

[0007] Step 1: synthesizing a DOPO-based silane coupling agent, modifying the DOPO-based silane coupling agent onto the surface of sodium-based vermiculite to obtain a flame-retardant modified vermiculite, and uniformly dispersing the flame-retardant modified vermiculite in an ethylene-vinyl alcohol copolymer matrix to prepare a flame-retardant barrier material;

[0008] The DOPO-based silane coupling agent is one of flame retardant coupling agent I, flame retardant coupling agent II, and flame retardant coupling agent III;

[0009] The chemical structural formula of the flame retardant coupling agent I is:

[0010]

[0011] The chemical structural formula of the flame retardant coupling agent II is:

[0012]

[0013] The chemical structural formula of the flame retardant coupling agent III is:

[0014]

[0015] Step 2: adopting eleven-layer co-extrusion blow molding film-forming process to prepare a single PE material eleven-layer composite structure film with a thickness of 50-200 μm; the single PE material eleven-layer composite structure film contains flame-retardant barrier material.

[0016] Preferably, the formula and dosage of the single PE material eleven-layer composite structure film are as follows:

[0017] First layer: the formula is 50-70wt% LDPE + 30-50wt% LLDPE, the dosage is 5-15wt%;

[0018] The second layer: the formula is 20-50wt% HDPE + 50-80wt% m-LLDPE, the dosage is 3-10wt%;

[0019] The third layer: the formula is 40-80wt% LDPE + 10-30wt% LLDPE + 10-30wt% m-LLDPE, and the dosage is 5-15wt%;

[0020] The fourth layer: the formula is 100wt% PE-g-MAH, the dosage is 1-5wt%;

[0021] The fifth layer: the formula is 90-95wt% LDPE + 5-10wt% EVOH, the dosage is 5-15wt%;

[0022] The sixth layer: the formula is 905-95wt% LDPE + 5-10wt% flame retardant barrier material, the dosage is 10-40wt%;

[0023] The seventh layer: the formula is 90-95wt% LDPE + 5-10wt% EVOH, the dosage is 5-15wt%;

[0024] The eighth layer: the formula is 100wt% PE-g-MAH, the dosage is 1-5wt%;

[0025] Ninth layer: the formula is 40-80wt% LDPE + 10-30wt% LLDPE + 10-30wt% m-LLDPE, and the dosage is 5-15wt%;

[0026] The tenth layer: the formula is 20-50wt% HDPE + 50-80wt% m-LLDPE, the dosage is 3-10wt%;

[0027] The eleventh layer: the formula is 25-45wt% LDPE+25-45wt% LLDPE+10-50% HDPE, and the dosage is 5-15wt%.

[0028] Preferably, the preparation method of the flame retardant coupling agent I is: an addition reaction is carried out between the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and the alkenyl functional group of methacryloxypropyltriethoxysilane to generate the flame retardant coupling agent I.

[0029] Preferably, the preparation method of the flame retardant coupling agent II is:

[0030] Step S4-1: generating a DOPO-based tertiary phosphine monomer by reacting the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the alkenyl functional group of allyl diphenylphosphine;

[0031] Step S4-2: utilizing the nucleophilic substitution reaction mechanism, the tertiary phosphine group of the DOPO-based tertiary phosphine monomer reacts with the bromine functional group of 3-bromopropyltrimethoxysilane to generate a flame retardant coupling agent II.

[0032] Preferably, the preparation method of the flame retardant coupling agent III is:

[0033] Step S5-1: generating a tri(DOPO-based) tertiary phosphine monomer by reacting the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the alkenyl functional group of triallylphosphine;

[0034] Step S5-2: utilizing the nucleophilic substitution reaction mechanism, the tertiary phosphine group of the tri(DOPO-based) tertiary phosphine monomer undergoes a quaternary phosphine reaction with the bromine functional group of 3-bromopropyltrimethoxysilane to generate a flame retardant coupling agent III.

[0035] The water vapor permeability of a single PE material eleven-layer composite structure film prepared according to the above method is 1.0-2.0 [g / (m 2 ·24h)], oxygen permeability is 1.0~1.5[cm 3 / (m 2 ·24h·0.1MPa)].

[0036] Beneficial Effects

[0037] The present invention first designs and synthesizes three new flame retardant coupling agents, then uses the flame retardant coupling agents to modify sodium vermiculite to prepare flame retardant modified vermiculite, and evenly disperses the flame retardant modified vermiculite in an ethylene-vinyl alcohol copolymer matrix to prepare a flame retardant barrier material (specifically: EVOH / flame retardant modified vermiculite composite material), and finally introduces the flame retardant barrier material into a PE co-extruded film, and adopts an eleven-layer co-extrusion blow molding film forming process to prepare an eleven-layer film product, which has excellent barrier properties, belongs to an ultra-high barrier material, and can be used as the best alternative in the field of dairy product packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the synthetic route of flame retardant coupling agent Ⅰ;

[0039] Figure 2 This is the synthetic route of flame retardant coupling agent II;

[0040] Figure 3 This is the synthetic route of flame retardant coupling agent III;

[0041] Figure 4 These are the performance test results of the eleven-layer co-extruded film. DETAILED DESCRIPTION

[0042] Experimental Example 1:

[0043] Preparation of flame retardant coupling agent I, such as Figure 1 As shown, the preparation method is: through the addition reaction of the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) with the alkenyl functional group of methacryloxypropyltriethoxysilane, a flame retardant coupling agent I is generated. The specific experimental steps are as follows: 2.2g DOPO and 30mL tetrahydrofuran are added to a four-necked bottle, stirred at room temperature until completely dissolved, and then 30mL methacryloxypropyltriethoxysilane solution (prepared by 2.9g methacryloxypropyltriethoxysilane and 30mL tetrahydrofuran) is added to the four-necked bottle, the temperature is raised to 75°C, stirred and refluxed for reaction for 5h, cooled to room temperature, the solvent is removed by rotary evaporation at 40°C in a water bath, and vacuum dried to obtain a flame retardant coupling agent I;

[0044] The nuclear magnetic resonance hydrogen spectrum of flame retardant coupling agent I is characterized as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 0.63-0.67 (t, 2H), 1.15-1.24 (m, 12H), 1.78-1.85 (m, 2H) , 2.78-2.85 (m, 3H), 3.72-3.80 (m, 6H), 4.09-4.13 (t, 2H), 7.26-8.05 (m, 8H, Ar-H).

[0045] Experimental Example 2:

[0046] Preparation of flame retardant coupling agent II, such as Figure 2 As shown, the preparation process is:

[0047] (1) preparing a DOPO-based tertiary phosphine monomer, wherein the preparation method comprises: reacting the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the alkenyl functional group of allyl diphenyl phosphine to generate a DOPO-based tertiary phosphine monomer, wherein the specific experimental steps are the same as those of the preparation experiment of the flame retardant coupling agent I, and the only difference is that 2.3 g of allyl diphenyl phosphine is used to replace 2.9 g of methacryloxypropyl triethoxysilane;

[0048] (2) Preparation of flame retardant coupling agent II, the preparation method of which is: using the nucleophilic substitution reaction mechanism, the tertiary phosphine group of the DOPO-based tertiary phosphine monomer and the bromine functional group of 3-bromopropyltrimethoxysilane undergo quaternary phosphination reaction to generate flame retardant coupling agent II, the specific experimental steps are: 2.2g of DOPO-based tertiary phosphine monomer and 50mL of N,N-dimethylformamide are added to a four-necked bottle, under nitrogen protection and mechanical stirring, the temperature is raised to 40°C, and after the temperature stabilizes, 1.0mL of 3-bromopropyltrimethoxysilane is added dropwise to the four-necked bottle, and the temperature is continued to be raised to 100°C and stirred for 12h, and after cooling, the mixture is rotary evaporated, washed with ethyl acetate, and vacuum dried to obtain flame retardant coupling agent II;

[0049] The nuclear magnetic resonance hydrogen spectrum of flame retardant coupling agent II is characterized as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 0.50-0.54 (t, 2H), 1.27-1.33 (m, 4H), 1.85-1.95 (m, 2H), 2.55-2.64 (m, 2H), 3.58 (s, 9H), 7.14-8.13 (m, 18H, Ar-H).

[0050] Experimental Example 3:

[0051] Preparation of flame retardant coupling agent III, such as Figure 3 As shown, the preparation process is:

[0052] (1) preparing a tri(DOPO-based) tertiary phosphine monomer, wherein the preparation method comprises: reacting the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the alkenyl functional group of triallylphosphine to generate a tri(DOPO-based) tertiary phosphine monomer, wherein the specific experimental steps are the same as those of the preparation experiment of flame retardant coupling agent I, and the only difference is that 0.5 g of triallylphosphine is used to replace 2.9 g of methacryloxypropyltriethoxysilane;

[0053] (2) Preparation of flame retardant coupling agent III, the preparation method of which is: using a nucleophilic substitution reaction mechanism, the tertiary phosphine group of tri(DOPO-based) tertiary phosphine monomer and the bromine functional group of 3-bromopropyltrimethoxysilane undergo quaternary phosphine reaction to generate flame retardant coupling agent III, the specific experiment is the same as the preparation experiment of flame retardant coupling agent II, the only difference is that 3.9g of tri(DOPO-based) tertiary phosphine monomer is used to replace the DOPO-based tertiary phosphine monomer;

[0054] The nuclear magnetic resonance hydrogen spectrum of flame retardant coupling agent III is characterized as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 0.50-0.55 (t, 2H), 1.26-1.34 (m, 6H), 1.76-2.03 (m, 6H) ), 2.47-2.75(m, 4H), 3.58(s, 9H), 3.95-4.03(m, 2H), 7.09-8.15(m, 24H, Ar-H).

[0055] Embodiment 1:

[0056] (1) Preparing flame-retardant modified vermiculite I, the preparation method of which is: modifying sodium-based vermiculite (containing hydroxyl functional groups in the zircon structure) with a flame-retardant coupling agent I to obtain flame-retardant modified vermiculite I, the specific experimental steps of which are: adding 2.0 g of flame-retardant coupling agent I and 20 mL of ethanol into a four-necked bottle, stirring and reacting in a 40° C. water bath for 1 h, then adding 0.5 g of sodium-based vermiculite into the four-necked bottle, heating to 60° C. and stirring and reacting for 3 h, cooling to room temperature and standing for 10 h, filtering, washing with deionized water, centrifuging, and vacuum drying to obtain flame-retardant modified vermiculite I;

[0057] An EVOH / flame retardant modified vermiculite I composite material is prepared. The preparation method is as follows: the flame retardant modified vermiculite I is dispersed in an ethylene-vinyl alcohol copolymer matrix to prepare the EVOH / flame retardant modified vermiculite I composite material. The specific experimental steps are as follows: 30 g of ethylene-vinyl alcohol copolymer resin and 5 g of flame retardant modified vermiculite I are added to a twin-screw extruder, and the EVOH / flame retardant modified vermiculite I composite material is prepared by blending, melting, extruding, and pelletizing the twin-screw extruder.

[0058] (2) preparing flame retardant modified vermiculite II, the preparation method of which is: modifying sodium-based vermiculite with flame retardant coupling agent II to obtain flame retardant modified vermiculite II, the specific experimental steps of which are the same as the preparation experiment of flame retardant modified vermiculite I, the only difference being that 3.4 g of flame retardant coupling agent II replaces 2.0 g of flame retardant coupling agent I;

[0059] An EVOH / flame retardant modified vermiculite II composite material is prepared. The preparation method is as follows: dispersing the flame retardant modified vermiculite II in an ethylene-vinyl alcohol copolymer matrix to prepare the EVOH / flame retardant modified vermiculite II composite material. The specific experimental steps are the same as the preparation experiment of the EVOH / flame retardant modified vermiculite I composite material, and the difference is only that the flame retardant modified vermiculite II is used to replace the flame retardant modified vermiculite I.

[0060] (3) preparing flame retardant modified vermiculite III, the preparation method of which is: modifying sodium-based vermiculite with flame retardant coupling agent III to obtain flame retardant modified vermiculite III, the specific experimental steps of which are the same as the preparation experiment of flame retardant modified vermiculite I, the only difference being that 2.0 g of flame retardant coupling agent I is replaced by 5.0 g of flame retardant coupling agent III;

[0061] An EVOH / flame retardant modified vermiculite III composite material is prepared. The preparation method is as follows: the flame retardant modified vermiculite III is dispersed in an ethylene-vinyl alcohol copolymer matrix to prepare the EVOH / flame retardant modified vermiculite III composite material. The specific experimental steps are the same as the preparation experiment of the EVOH / flame retardant modified vermiculite I composite material, and the difference is only that the flame retardant modified vermiculite III is used to replace the flame retardant modified vermiculite I.

[0062] The preparation method of sodium vermiculite is as follows: add vermiculite powder to 1 mol / L sodium chloride aqueous solution (the content of vermiculite is controlled to be 20 wt%), stir the reaction at room temperature for 12 hours, centrifuge (use 0.1 mol / L silver nitrate solution to detect the presence of Cl in the supernatant) - ), drying, and grinding in a ball mill to prepare sodium vermiculite;

[0063] Among them, ethylene-vinyl alcohol copolymer resin (EVOH) was purchased from Guangzhou Best New Material Technology Co., Ltd., and its brand is ET3803RB; vermiculite powder was purchased from Lingshou County Mineral Products Processing Plant in Hebei Province, and its impurity content was less than 0.5%;

[0064] The process parameters of the twin-screw extruder are set as follows: the temperatures of zones 1-3 are 150°C, 170°C, and 195°C, respectively, and the rotation speed is 40 r / min.

[0065] Embodiment 2:

[0066] (1) Preparation of modified eleven-layer co-extruded film I: W&H ( Anhui Zijin New Materials Technology Co., Ltd.) made its own 11-layer blown film production line to prepare a modified 11-layer co-extruded film I with a thickness of 80 μm. The specific steps are as follows:

[0067] Step 1: plasticize and extrude the mixed raw materials in the extruder according to the formula of each layer in Table 1; count the weight of the raw materials passing through per unit time, adjust the speed of the extruder and the pressure of the die outlet by the speed of the metering pump, keep the raw materials flowing out of the die stable, and further plasticize the raw materials;

[0068] Step 2: Add the prepared mixed materials into the hoppers of the corresponding layers of the eleven-layer co-extrusion film blowing machine according to the mass ratio of the eleven-layer distribution in Table 1, and heat them according to the process parameters in Table 1. After the temperature reaches the required temperature, the mixed materials enter the screw and melt, and start the W&H equipment 11-layer film blowing production line for extrusion and blowing;

[0069] Step 3: After passing through the bubble stabilizing frame to the upper drawing guide roller, the outer layer is subjected to corona treatment, and then the second drawing is carried out. After passing through the guide roller, the third drawing is carried out, and folding and winding are carried out to obtain the modified eleven-layer co-extruded film I.

[0070] Table 1 Experimental formula and process parameters of modified eleven-layer co-extrusion film I

[0071]

[0072]

[0073] (2) Preparation of modified eleven-layer co-extruded film II: Only EVOH / flame retardant modified vermiculite II composite material is used to replace the EVOH / flame retardant modified vermiculite I composite material in the modified eleven-layer co-extruded film I to prepare a modified eleven-layer co-extruded film II.

[0074] (3) Preparation of modified eleven-layer co-extruded film III: Only EVOH / flame retardant modified vermiculite III composite material was used to replace the EVOH / flame retardant modified vermiculite I composite material in the modified eleven-layer co-extruded film I to prepare a modified eleven-layer co-extruded film III.

[0075] (4) Preparation of eleven-layer co-extruded film: EVOH was used to replace the EVOH / flame-retardant modified vermiculite I composite material in the modified eleven-layer co-extruded film I, and an eleven-layer co-extruded film was prepared according to the same experimental steps and reaction conditions as a comparative example.

[0076] The specifications and manufacturers of the raw materials used in the specific implementation are shown in Table 2;

[0077] Table 2 Experimental raw materials

[0078]

[0079] Performance Test:

[0080] (1) Barrier properties: The barrier properties of the samples were tested using a Y110 oxygen permeability tester and a TC-03 water vapor permeability tester in accordance with GB / T 1038-2000 and GB / T 1037-2021 respectively;

[0081] (2) Flame retardant properties: A rectangular sample of 2 cm × 4 cm was fixed vertically and burned, and the ignition time of the sample was recorded;

[0082] (3) Mechanical properties: A 30 mm × 5 mm sample was fixed on an Instron 5565 universal tensile testing machine and subjected to a tensile test at a tensile rate of 5 mm / min. The tensile strengths in the longitudinal and transverse directions were recorded respectively.

[0083] The above experimental results are shown in Table 3 and Figure 4 .

[0084] Table 3 Performance test results of eleven-layer co-extruded film

[0085]

[0086] The following conclusions can be drawn from the results of performance testing:

[0087] (1) The three flame-retardant barrier materials (i.e., EVOH / flame-retardant modified vermiculite I composite material, EVOH / flame-retardant modified vermiculite II composite material, and EVOH / flame-retardant modified vermiculite III composite material) can significantly improve the barrier performance of a single PE material eleven-layer composite structure film, and the improvement effects of the three flame-retardant barrier materials are not much different;

[0088] (2) All three flame-retardant barrier materials can significantly enhance the flame retardancy of the single PE material eleven-layer composite structure film, and the improvement effect of EVOH / flame-retardant modified vermiculite III composite material is the best.

Claims

1. A method for preparing a single PE material eleven-layer composite structure film, characterized in that: The following steps are involved: Step 1: synthesizing a DOPO-based silane coupling agent, modifying the DOPO-based silane coupling agent onto the surface of sodium-based vermiculite to obtain a flame-retardant modified vermiculite, and uniformly dispersing the flame-retardant modified vermiculite in an ethylene-vinyl alcohol copolymer matrix to prepare a flame-retardant barrier material; The DOPO-based silane coupling agent is one of flame retardant coupling agent I, flame retardant coupling agent II, and flame retardant coupling agent III; The chemical structural formula of the flame retardant coupling agent I is: The chemical structural formula of the flame retardant coupling agent II is: The chemical structural formula of the flame retardant coupling agent III is: Step 2: adopting eleven-layer co-extrusion blow molding film-forming process to prepare a single PE material eleven-layer composite structure film with a thickness of 50-200 μm; the single PE material eleven-layer composite structure film contains flame-retardant barrier material.

2. The method for preparing a single PE material eleven-layer composite structure film according to claim 1, characterized in that: The formula and dosage of the single PE material eleven-layer composite structure film are as follows: First layer: the formula is 50-70wt% LDPE + 30-50wt% LLDPE, the dosage is 5-15wt%; The second layer: the formula is 20-50wt% HDPE + 50-80wt% m-LLDPE, the dosage is 3-10wt%; The third layer: the formula is 40-80wt% LDPE + 10-30wt% LLDPE + 10-30wt% m-LLDPE, and the dosage is 5-15wt%; The fourth layer: the formula is 100wt% PE-g-MAH, the dosage is 1-5wt%; The fifth layer: the formula is 90-95wt% LDPE + 5-10wt% EVOH, the dosage is 5-15wt%; The sixth layer: the formula is 90-95wt% LDPE + 5-10wt% flame retardant barrier material, the dosage is 10-40wt%; The seventh layer: the formula is 90-95wt% LDPE + 5-10wt% EVOH, the dosage is 5-15wt%; The eighth layer: the formula is 100wt% PE-g-MAH, the dosage is 1-5wt%; Ninth layer: the formula is 40-80wt% LDPE + 10-30wt% LLDPE + 10-30wt% m-LLDPE, and the dosage is 5-15wt%; The tenth layer: the formula is 20-50wt% HDPE + 50-80wt% m-LLDPE, the dosage is 3-10wt%; The eleventh layer: the formula is 25-45wt% LDPE+25-45wt% LLDPE+10-50% HDPE, and the dosage is 5-15wt%.

3. The method for preparing a single PE material eleven-layer composite structure film according to claim 1, characterized in that: The preparation method of the flame retardant coupling agent I is as follows: the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is subjected to an addition reaction with the alkenyl functional group of methacryloxypropyltriethoxysilane to generate the flame retardant coupling agent I.

4. The method for preparing a single PE material eleven-layer composite structure film according to claim 1, characterized in that: The preparation method of the flame retardant coupling agent II is: Step S4-1: generating a DOPO-based tertiary phosphine monomer by reacting the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the alkenyl functional group of allyl diphenylphosphine; Step S4-2: utilizing the nucleophilic substitution reaction mechanism, the tertiary phosphine group of the DOPO-based tertiary phosphine monomer reacts with the bromine functional group of 3-bromopropyltrimethoxysilane to generate a flame retardant coupling agent II.

5. The method for preparing a single PE material eleven-layer composite structure film according to claim 1, characterized in that: The preparation method of the flame retardant coupling agent III is: Step S5-1: generating a tri(DOPO-based) tertiary phosphine monomer by reacting the PH bond of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with the alkenyl functional group of triallylphosphine; Step S5-2: utilizing the nucleophilic substitution reaction mechanism, the tertiary phosphine group of the tri(DOPO-based) tertiary phosphine monomer undergoes a quaternary phosphine reaction with the bromine functional group of 3-bromopropyltrimethoxysilane to generate a flame retardant coupling agent III.

6. A single PE material eleven-layer composite structure film prepared by the method according to any one of claims 1 to 5, characterized in that: The water vapor permeability of the single PE material eleven-layer composite structure film is 1.0-2.0 [g / (m 2 ·24h)], oxygen permeability is 1.0~1.5[cm 3 / (m 2 ·24h·0.1MPa)].

7. Application of the single PE material eleven-layer composite structure film according to claim 6 in the field of dairy product packaging.

Citation Information

Patent Citations

  • High-barrier recyclable composite film made of single material

    CN116604907A

  • Silane coupling agent containing DOPO group and preparation method thereof

    CN101792537A

  • Vermiculite-based composite flame retardant and preparation method thereof

    CN104072805A

  • Preparation method of surface modification and flame retardance enhancement dual-function nano hydroxyl zinc stannate flame retardant

    CN105295100A

  • Preparation method of flame retardance modified wood fiber composite phenolic foam

    CN107501856A

Cited By

  • Co-extruded film, preparation process and application of co-extruded film in new energy battery

    CN121801307A

  • Co-extruded film, preparation process and application in new energy battery

    CN121801307B